Research trends in sustainable quality education: A bibliometric approach to technology integration in learning - Yudaningsih, Nunik (Universitas Jambi, Indonesia, 2025)
This study uses bibliometric methods to investigate global research trends on integrating technology in sustainable quality education. Drawing on 2010–2025 Scopus-indexed publications, the study analyzes patterns in authorship, geographic distribution, and conceptual themes. Utilizing VOSviewer and Bibliometrix, it maps keyword co-occurrences and collaboration networks. The findings reveal accelerated research growth post-2020, with significant contributions from the Global South and emerging interdisciplinary themes such as equity, digital sustainability, and eco-pedagogy. The investigation emphasizes the value of systemic integration between education, technology, and sustainability frameworks, offering insights for future research, policy, and educational innovation.